SAKTI: THE FEMININE ASPECT OF GOD IN INDIAN TRADITION - Madtha, William (Journal of Dharma, 1980)
One of the happy signs of the modern age of aggiornamento and ecumenism is the gradual but profound change of status quo in various religions, thanks to the acceptance of plurality of cultures and, therefore, of the religious faiths tool by modern man, willy-nilly! Though the ultimate content of all the diverse faiths is the same thrilling Mysterion at the deep level, its realization at the surface level, however, is multifarious in form.